Faktor-Faktor Penyebab Keterlambatan Penyediaan Rekam Medis Rawat Jalan di Rumah Sakit - Fajria Nur Rahmah; Maya Weka Santi; Ervina Rachmawati; Demiawan Rachmatta Putro Mudiono (FORIKES, 2022)
Previous studies have shown that there is a delay in the provision of outpatient medical records in hospitals across Indonesia, where the provision time is not in accordance with established standards. So a study is needed to find out the factors that cause delays in the provision of outpatient medical records in hospitals. The method used is a literature review by identifying 30 articles from Google Scholar and the Garuda Portal. The results of the data abstraction of 30 selected literature can be summarized by the factors causing the delay in the provision of outpatient medical records at hospitals in terms of the 5M element, the man factor, which is high workload and the number of medical record human resources is small, the money factor is the budget that has not been used properly, the material factor namely the medical record file was not found on the filing rack, material factors, namely the medical record file was not found on the filing rack, the machine factor, namely the condition and location of the filing room was not supportive.Keywords: medical record; provision; lateness ABSTRAK Penelitian terdahulu menunjukkan adanya keterlambatan penyediaan rekam medis rawat jalan di rumah sakit yang tersebar di Indonesia, dimana waktu penyediaan tidak sesuai dengan standar yang telah ditetapkan. Maka diperlukan studi untuk mengetahui faktor-faktor yang menyebabkan keterlambatan penyediaan rekam medis rawat jalan di rumah sakit. Metode yang digunakan yaitu literature review dengan mengidentifikasi 30 artikel dari Google Scholar dan Portal Garuda. Hasil abstraksi data 30 literatur terpilih dapat dirangkum faktor penyebab keterlambatan penyediaan rekam medis rawat jalan di rumah sakit ditinjau dari unsur 5M, pada faktor man yaitu beban kerja tinggi dan jumlah SDM perekam medis sedikit, faktor money adalah anggaran yang belum digunakan dengan baik, faktor material yaitu berkas rekam medis tidak ditemukan di rak filing, faktor material yaitu berkas rekam medis tidak ditemukan di rak filing, faktor machine yaitu kondisi dan lokasi ruang filing kurang mendukung.Kata kunci: rekam medis; penyediaan; keterlambatan